Nootropics: Phytochemicals with Neuroprotective and Neurocognitive Enhancing Properties - Crespo-Bujosa, Héctor B.; Suárez Rodríguez, Ramón L.F. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Introduction. Neurological chronic conditions represent a healthcare concern worldwide. They hinder a person’s functionality affecting family, social interactions, as well as academic and work performance. In addition, the complexity of these illnesses and the variable response to treatments, as well as the side-effects, call for the research and implementation of phytochemicals known as Nootropics to form part of an integrative treatment. Aim. To present the influence of nootropics on neuroprotection and neurocognition. Material and methods. Analysis of literature data found in the PubMed database. Results. Nootropics, which can be synthetic or natural, possess properties that translate in enhancement of mental or neurocognitive functions. Within the natural options, vitamins, plants and even fungi have been found to produce cognitive enhancement with less side-effects. Continuing research has shown promising therapeutic uses for B vitamins, Hericium herinaceus and Ginkgo biloba as coadjuvants in the treatment of neurologic chronic conditions to improve an individual’s neurocognitive functions and quality of life. Conclusion. Nootropics open the door for new research, clinical implementation and promotion of integrative health especially in cognitive neuroscience by implementing products of natural sources. This is particularly important in order to identify side-effects, drug-herb interactions, proper posology and synergic actions that may prove to improve neurocognitive functioning and health improvement.
Keywords: cognitive enhancers; phytochemicals; neurologic conditions; B vitamins; Hericium erinaceus; Ginkgo biloba